Temperature-dependent optical properties of hybrid organic–inorganic perovskite single crystals (CH3NH3PbI3 and CH3NH3PbBr3). (13th June 2019) - Park, Sangheon; Seo, Yu-Seong; Ahn, Chang Won; Woo, Won Seok; Kyhm, Jihoon; Lee, Sang A; Kim, Ill Won; Hwang, Jungseek
Abstract: We investigated the temperature-dependent optical properties of methylammonium lead iodide (MAPbI3 : CH3 NH3 PbI3 ) and bromide (MAPbBr3 : CH3 NH3 PbBr3 ) single crystals using optical spectroscopy and photoluminescence (PL) techniques. We obtained the optical conductivity from the measured reflectance spectra of the single crystals at various temperatures using a Kramers–Kronig relation and measured their PL spectra at selected temperatures. We observed structural phase transitions and a mixed-structure phase from the infrared-active phonon modes in the measured optical data. In the mixed phase, we observed unsystematic temperature-dependent bandgap behavior in both optical and PL spectra. The unsystematic bandgap behavior can be understood by taking into account both the contributions of thermal effect and structural phase to the size of the bandgap in the temperature region of the mixed structural phase or the structural phase transition. Interestingly, we also observed quantitative differences in those optical and PL properties between thin film and single crystal samples. We expect that our results will supply helpful information for further development of hybrid organic–inorganic perovskite solar cells.